Environmental Accounting of the Yellow-Tail Lambari Aquaculture: Sustainability of Rural Freshwater Pond Systems - Fonseca, Tamara [UNESP]; Valenti, Wagner C. [UNESP]; Giannetti, Biagio F.; Gonçalves, Fernando H.; Agostinho, Feni (MDPI, 2022)
Freshwater pond aquaculture is the prevailing fish culture system worldwide, especially in developing countries. The sustainability of such systems has not been assessed and it can be improved based on suitable scientific analyses. In the present study, we apply the emergy synthesis to assess the sustainability of lambari aquaculture, used as a model of freshwater pond monoculture in Brazil, to identify the key practices, and to propose changes to improve them towards sustainability. As a study model, nine semi-intensive lambari farms operating at three levels of management were evaluated: low (LC), moderate (MC) and high (HC) control. Results showed that the main inputs for LC were services (27–46%), feed (7–39%) and water (15–21%), while for the MC and HC farms, they were feed (35–49% and 17–48%, respectively) and services (33–39% and 26– 36%, respectively). All farms required more than 60% of their emergy from purchased inputs, resulting in low emergy sustainability index (ESI = 0.1–0.5). Increasing juvenile productivity, using superficial water instead of springwater, controlling pond fertilization and replacing animal protein in diet composition by vegetable sources can lead systems to higher efficiency and resilience, increasing sustainability.
Keywords: Emergy; Fish production; Rural aquaculture; Water use